The Slovenian Art History Textbook in Comparison to Polish Textbooks: Authorship and Content, Didactic Structure and Publishing Circumstances - Dolšina, Marjana (Journal of Education Culture and Society, 2020)
The paper analyses two concepts of art history textbooks for secondary schools. It discusses their role in the learning and teaching process of art history and related school subjects within the formal educational programmes in Slovenia and their didactic structure. The comparison between one Slovenian and two Polish textbooks might contribute to better understanding of the present situation regarding art history textbook production in Slovenia, which is a result of several factors: the historical continuity of textbook writing and research in textbook didactics, the current school policy and fi nancial competition on the textbook market. Its intention is also to clarify the idea of didactic transformation of the art history contents from the challenging scientifi c texts to a form suitable for secondary school students who are textbooks’ main target audience.